Islamic Higher Education and Religious Transformation of The Muslim Community’s Surrounding - Nur Kafid; Nur Rohman (Jurnal Pendidikan Islam, 2018)
The emergence and the development of PTKI (Perguruan Tinggi Keagamaan Islam/Islamic Higher Education) in Indonesia are much influenced by social, political, ideology and religious condition of the community’s surrounding. Since its emergence, PTKI is always preparing and fixing all the things in order to be able to answer the society’s needs. Hereby, this study aims to investigate the contribution of IAIN (Institut Agama Islam Negeri/State Islamic Institute) Surakarta to the development of Muslim community’s religiosity within its surroundings, and its various supported and inhibited factors. Based on the qualitative method, the result of this study revealed that IAIN Surakarta had real contribution to the development of the Muslim religiosity in Pucangan, Kartasura. The emerging of religious education institutions, arising from various religious activities, and raising people's awareness on the importance of religious education can be used as indicators of the successfulness of IAIN Surakarta’s as an agent of Islamization, as well as an agent of social change, especially in the transformation process of religious values to its surrounding community.